PRODUK HANDMADE PERSONAL CARE YANG INOVATIF UNTUK MENDUKUNG RELAKSASI INDIVIDU - Anastasia Amelia Winardi; Christian Anggrianto (Jurnal Vicidi, 2016)
With the raise of expectation and pressure in everyday life, each individu need a solution to release their stress. Bathing has become a relaxation time for an individual. Therefore, the quality of the relaxation aspect in any body care product should be enhanced. Designing the natural skin care products which are more attractive and trendy is expected to fulfill the needs of the fullfilled and experiencer as the target of these products. There are several theories that will be used in this paper such as 4 Lenses of Innovation, Ten Types of Innovation, SCAMPER, and VALS. These theories will be used to guide the business plan making of the natural skin care products.